2012
DOI: 10.1111/j.1600-0668.2012.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Are rocket mud stoves associated with lower indoor carbon monoxide and personal exposure in rural Kenya?

Abstract: The rocket mud stoves (RMS) were associated with lower CO concentrations compared to three-stone stoves. However, the difference in concentrations was modest and concentrations in both stove groups exceeded the WHO guideline of 7 μg/m(3) , suggesting the unvented RMSs on their own are unlikely to appreciably benefit health in this population. Greater air quality benefit could be realized if the stoves were complemented with behavior change, including education on extinguishing fire when not in use as well as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…The assessment of HAP among control and intervention households showed an overall reduction of 48% of 24-h PM 2.5 among intervention households, which was comparable to reductions in household air pollution for rocket stove interventions in Ghana (52%) and Kenya (33%) [22], [45]. Indoor cooking with the intervention stoves as opposed to the traditional stove was associated with a 37% reduction in 24-h PM 2.5 , which was of borderline significance.…”
Section: Discussionmentioning
confidence: 76%
“…The assessment of HAP among control and intervention households showed an overall reduction of 48% of 24-h PM 2.5 among intervention households, which was comparable to reductions in household air pollution for rocket stove interventions in Ghana (52%) and Kenya (33%) [22], [45]. Indoor cooking with the intervention stoves as opposed to the traditional stove was associated with a 37% reduction in 24-h PM 2.5 , which was of borderline significance.…”
Section: Discussionmentioning
confidence: 76%
“…In rural Upper West Ghana, a study measuring the effects of a brick and mortar chimney stove intervention found that there was no significant difference in CO exposure compared to the control group, as measured during uncontrolled cooking tests [33]. Ochieng and colleagues [34] found median personal CO concentrations of primary cooks of 6.5 ppm in rural Kenyan homes using TSFs, and 4.4 ppm in homes using improved mud stoves. In Guatemala, in a colder climate with more indoor cooking, adult women cooks in the control group of the RESPIRE study experienced average 48 h exposures of 4.8 ppm (SD = 3.6), while the group with an improved plancha stove had an average exposure of 2.2 ppm (SD = 2.6).…”
Section: Comparisons With Previous Personal Co Exposure Resultsmentioning
confidence: 99%
“…TZOA-R had a firmware bug in the internal Real Time Clock, resulting in poor time stamp mapping). However, this is not the case of the EL-USB-CO, which is an established device that has been previously used in household air pollution studies as a personal monitor 53,54 and as an indoor monitor 16,55,43,56,57 . Generally it has been used to measure CO for periods of 24h or less, although three studies have attempted to use it for longer periods 43,54,56 .…”
Section: Discussionmentioning
confidence: 99%